KATEKIS DAN PASTORAL POLITIK - Inosentius Mansur (Jurnal Alternatif Wacana Ilmiah Interkultural, 2014)
The notion of politic from Fr. Ino takes account not only of the personal and inter-personal aspect of Christian faith buat also ofits public and “political" aspects. He is aware that to make an option for the poor that counts very much the pastoral shape and involvements ofthe Chatechists in the church.Spirituality andjustice that shapes verymuch the model ofthe Chatechist in the church is an original and challenging contribution to the church as a whole No animation in the church without advocation.A chatechist in the church should stress the need fora transformation ofsocietyby“kingdom values', advocationg and discussing an alternative approach to politic, economics and theology itself as well as an alternative model of the church.The author would like to stress that spirituality andjustice verymuch linked to politics are topics ofcentral concern to the church today.Politic for a chatechist in the church is seen as an articulation of a basic religious outlook or spirituality.